Nutrition of draught oxen in semi-arid West Africa. 2. Effect of work on intake, apparent digestibility and rate of passage of food through the gastro-intestinal tract in draught oxen given crop residues - Fall, Abdou; Pearson, R.A.; Lawrence, P.R.; Fernández Rivera, S. (1997)
Two experiments were conducted to investigate the relationships between work and intake and digestion of food by draught oxen given millet stover. In the first experiment, intake of millet stover, water intake, live weight, plasma concentrations of triiodothyronine, thyroxine and urea-nitrogen were measured in 18 animals that worked 0, 2 or 4 h/day in sequence during three 3-week experimental periods. Digestibility and rate of passage of food residues through the digestive tract were measured in a second experiment on 12 animals working either 0, 2.5 or 5 h/day in sequence during three 2-week experimental periods. Feeding behaviour was monitored on six animals working either 0, 2.5 or 5 h/day. Work did not affect intake of millet stover, apparent digestibilities and the rate of passage of digesta through the gastro-intestinal tract. This suggests that the nutrient supply from intake of roughages by working oxen is unlikely to be sufficient to compensate for the extra energy expended during work. Food intake was affected by the quality of the millet stover offered. The level of intake of millet stover was proportional to the amount of leaves in the stover. Food intake increased also as work progressed. However, animals mobilized their body reserves to perform work. Animals consumed more water on working days than on day they were at-rest in shade. The heat stress that working animals were subjected to did not appear to interfere with their digestive function.